2014
DOI: 10.2478/nsad-2014-0015
|View full text |Cite
|
Sign up to set email alerts
|

Images of alcoholism among adolescents in individualistic and collectivistic geographies

Abstract: Aim This article compares adolescents' images of alcoholism in two different drinking geographies, namely Helsinki (Finland) and Turin (Italy), with the aim to better understand the persisting variance in youth drinking within Europe. Design Altogether 28 focus group interviews were conducted at schools among 15-year-old pupils (N=145). To assure reliable qualitative comparison across language boundaries, we applied a structured qualitative focus-group methodology called the Reception Analytical Group Interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
(15 reference statements)
2
23
0
Order By: Relevance
“…Young people are not forced to speak about their behaviour unless they want to do it, anyway by talking about clips they apply their personal images based on their own direct and indirect experiences. This method is particularly useful when young people who do not yet have personal experience with drinking are involved (Rolando & Katainen, 2013;Sulkunen & Egerer, 2009;Törrönen, 2002). After all to have the certainty that the interviewees' statements match their behaviour is never possible in social research (Douglas, 1976), though using indirect questions, interviewees may feel less tempted to provide social acceptable answers to the interviewer.…”
Section: Sample and Methodologymentioning
confidence: 97%
See 1 more Smart Citation
“…Young people are not forced to speak about their behaviour unless they want to do it, anyway by talking about clips they apply their personal images based on their own direct and indirect experiences. This method is particularly useful when young people who do not yet have personal experience with drinking are involved (Rolando & Katainen, 2013;Sulkunen & Egerer, 2009;Törrönen, 2002). After all to have the certainty that the interviewees' statements match their behaviour is never possible in social research (Douglas, 1976), though using indirect questions, interviewees may feel less tempted to provide social acceptable answers to the interviewer.…”
Section: Sample and Methodologymentioning
confidence: 97%
“…During the FGs, participants do not express only their own interpretations, but discuss them with the other interviewees. This comparison enables us to address the different positions that come into play more effectively and look at negotiation processes (Rolando & Katainen, 2013).…”
Section: Sample and Methodologymentioning
confidence: 99%
“…In this context research has shown that a young age is generally regarded as risky in modern society. The teenage years are frequently depicted as years of agitation, experimenting and rebellion(Frønes, 2011;Room, 2012).While using alcohol or drugs in this period of life is a sign of maturity, young people also enter a danger zone in their efforts to mature(Demant & Järvinen, 2006;Rolando & Katainen, 2014;Room, 2012).The discourse of "youth as an age of risk" offers certain subject positions. Within this discourse young NAV users are positioned with limited responsibility, while the counsellor is positioned with responsibility for the young, vulnerable user.…”
mentioning
confidence: 99%
“…In Europe, according to the 2015 European School Survey Project on Alcohol and Other Drugs (ESPAD), 35% of 15 to 16-year-old adolescents reported BD (ESPAD, 2016), while in Spain, the percentage stood slightly lower, at 32.2% of students between 14 and 18 years of age (ESTUDES, 2018). However, previous research has suggested a convergent trend in youth drinking cultures, since BD has increased in southern Europe and decreased in the north (Rolando & Katainen, 2014a;Pape, Rossow & Brunborg, 2018). Despite these global trends of current adolescent cultures, the ways in which young people are socialised regarding drinking customs are still very different among the countries of Europe (Katainen et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Despite these global trends of current adolescent cultures, the ways in which young people are socialised regarding drinking customs are still very different among the countries of Europe (Katainen et al, 2015). A study carried out by Rolando and Katainen (Rolando et al, 2014a), where they compare Italian and Finnish adolescents, established that both have very different expectations about the consequences of drinking, as well as the kinds of drinks, quantities or with whom they drink alcohol. In Spain, BD is associated with the "Botellón", consisting of drinking alcohol excessively in public places with friends during weekend nights (Romo-Avilés et al, 2016ab), using it as a synonym for intoxication-oriented drinking (Guise et al, 2007).…”
Section: Introductionmentioning
confidence: 99%